Mechanisms Governing Immunotherapy Resistance in Pancreatic Ductal Adenocarcinoma - Zoe C. Schmiechen; Zoe C. Schmiechen; Ingunn M. Stromnes; Ingunn M. Stromnes; Ingunn M. Stromnes; Ingunn M. Stromnes (Frontiers in Immunology, 2021)
Pancreatic ductal adenocarcinoma (PDA) is a lethal malignancy with an overall 5-year survival rate of 10%. Disease lethality is due to late diagnosis, early metastasis and resistance to therapy, including immunotherapy. PDA creates a robust fibroinflammatory tumor microenvironment that contributes to immunotherapy resistance. While previously considered an immune privileged site, evidence demonstrates that in some cases tumor antigen-specific T cells infiltrate and preferentially accumulate in PDA and are central to tumor cell clearance and long-term remission. Nonetheless, PDA can rapidly evade an adaptive immune response using a myriad of mechanisms. Mounting evidence indicates PDA interferes with T cell differentiation into potent cytolytic effector T cells via deficiencies in naive T cell priming, inducing T cell suppression or promoting T cell exhaustion. Mechanistic research indicates that immunotherapy combinations that change the suppressive tumor microenvironment while engaging antigen-specific T cells is required for treatment of advanced disease. This review focuses on recent advances in understanding mechanisms limiting T cell function and current strategies to overcome immunotherapy resistance in PDA.